Evaluation of capsicum (Capsicum annuum L.) genotypes for variety improvement - Bhattarai, D. R.; Maharjan, S. K.; Gautam, I. P.; Subedi, S.; Pokhrel, S. (Journal of Agriculture and Forestry University, 2020)
An experiment was done at Horticulture Research Division, Nepal Agricultural Research Council (NARC), Khumaltar, Nepal under polyhouse condition to access different traits of six capsicum genotypes: HRDCAP-001, HRDCAP-003, HRDCAP-004, HRDCAP-005, HRDCAP-006, and California Wonder (check variety) with the objective to evaluate yield and quality. The experiment was done by using Randomized Complete Block Design (RCBD) with four replications for each treatment. All the collected data were analyzed by using Gentstat statistical software package. Results revealed that tested genotypes were significantly different (p<0.05) in terms of traits characteristics considered for the study. Accordingly, California Wonder was the best for fruit length (86.11 mm), fruit width (70.45 mm), and fruit weight (126.12 g) while HRDCAP-001 was superior in pericarp thickness (6.44 mm), fruit yield (2.46 kg per plant; 68.3 t/ha) and shelf life (6.80 days). California Wonder had lowest physiological weight loss at different days after harvest. This study recognizes HRDCAP-001 to be a promising genotype. Hence, there is a possibility to release this genotype as a variety for commercial cultivation, however, a multi location trial prior to its release is deemed necessary. Furthermore, all evaluated genotypes through this research could be utilized for capsicum breeding in Nepal.